Postcolonial Europe in the crucible of cultures : reckoning with God in a world of conflicts - Haers, Jacques.; Hintersteiner, Norbert, 1963-; Schrijver, Georges de. (Currents of Encounter, 2007)
Over the past forty years Europe has grown as a global presence and today it plays an important role in a variety of ways: politically, socially, economically, and culturally. European theologians have no choice but to take cognizance of this fact and respond to the broad social challenges by clarifying their views on God and being a prophetic voice in cultural, political and social decision-making. The authors in this volume take up four main contemporary global challenges, id est globalization, violence, gender, and the environment, and the volume provides its readers with first-rate theological reflections in Europe. The articles offered here are the result of an intensive workshop held in Leuven in September 2004 and are sponsored by the European Commission and the VLIR, as part of a three-year study program on the understanding of God in Europe.